Promoting Health Improvement of Indonesian Migrant Workers and Their Children in Kuala Lumpur, Malaysia - Porusia, Mitoriana; Dewi, Listiana Masyita; Kusudaryati, Dewi Pertiwi Dyah; Widyastuti, Yuli; Mahmudi, Lia Kicky; Prasesti, Wulan; Insyiroh, Fahwa Nyssa; Haryanti, Niken Diah; Nuralam, Muhammad Fathan; Putri, Nastiti Farasvita; Azahra, Miranda; Izdhihar, Rafif Ryandra; Setiyaningrum, Zulia; Buhari, Siti Sabariah (UI Scholars Hub, 2023)
This article discusses the health promotion program among Indonesian migrant workers and their children living in Kuala Lumpur, Malaysia, aiming for a better awareness of their health condition. In particular, this article describes and analyzes the community engagement program in Sekolah Indonesia Kuala Lumpur (SIKL) and Muhammadiyah Malaysia (PCIM) to provide health education and screening. Based on the preliminary study, Indonesian migrant workers and their families have limited access to healthcare facilities and programs. The program covers topics such as healthy reproduction and sexual vigilance for the youth, well-being and healthy lifestyles, as well as the importance of basic health screening. The program employs a qualitative study, employing the pre- and post-tests to measure the increase of knowledge before and after the program using descriptive statistics. As a result, an increase in awareness regarding health conditions among the youth can be identified after being exposed to the program. Meanwhile, the health screening program successfully identifies the health profile of migrant workers: a tendency to be overweight and a suffer from degenerative diseases. The screening results made them to be more aware of their health condition. The program was well received, as shown by the number of participants and further requests for a regular health screening. This finding indicates that future studies are required, to identify the daily diet of migrant workers and other health indicators. A similar phenomenon might occur with migrant workers globally, showing the importance of the provision of access and health programs for them.